Electrical and Optical Characterization of Gliding Arc Discharge (GAD) Operated at Line Frequency (50 Hz) Power Supply - Dhungana, S.; Guragain, R. P.; Baniya, H. B.; Panta, G. P.; Chhetri, G. K.; Subedi, D. P. (Journal of Nepal Physical Society, 2020)
In this study, an atmospheric alternating-current gliding arc device using line frequency (50 Hz) has been designed for the generation of various reactive species in different working gases. Electrical characteristics of the generated discharge are investigated by oscilloscope while the optical characteristics are analyzed using optical emission spectroscopy. The role of different working gases (oxygen, argon and air) on discharge voltages and power consumption per cycle in the discharge are calculated and compared. Electron density and electron temperature of the discharge are estimated by electrical and optical method respectively. The production of reactive species in the discharge is affirmed by optical emission spectroscopy. The outcomes of the results confirm that the GAD can generate non-equilibrium plasma having reactive nitrogen and oxygen species (RONS) which are essential for plasma chemistry applications.